Criminological Review of Fictitious Food Orders Through Online Ride-Hailing Applications - Malik, Sonang Mauludin (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
The rapid growth of online ride-hailing applications in Indonesia has revolutionized transportation and food delivery services but has also given rise to fraudulent practices such as fictitious food orders. This study aims to analyze such crimes through the lens of criminology and victimology, focusing on offender motives, modus operandi, and impacts on victims. Drawing on criminological theories including Differential Association and Rational Choice, the research employs a qualitative literature review of scholarly works, legal documents, case records, and credible news sources. Findings reveal that fictitious orders are driven by motives ranging from personal revenge and economic gain to psychological gratification, facilitated by weak verification systems and anonymity. The study contributes to theory by integrating criminological perspectives with digital crime analysis and offers practical recommendations for stricter identity verification, limiting cash-on-delivery transactions, and enhancing fraud reporting mechanisms. These insights are expected to guide platform operators, policymakers, and law enforcement in preventive strategies.